(untitled) (Research, Society and Development, 2022)
Several types of services and companies depend on the means of transport to send and receive, with safety and quality, their products and raw materials. Among these mentioned features, cargo transport stands out, mainly in the region of Santos, as it is linked to the Port Terminal of the region. Given the significant use of road transport, companies are always looking for ways to reduce time and cost in the country’s transport processes, in order to improve the logistics that involve the delivery of the final product. In 2020, the Port of Santos recorded a net profit of approximately 120 million reais, traffic of 1.1 million passengers and 120 million tons handled. Taking into account the magnitude of the Port Complex of Santos, several processes occur simultaneously within the 53 port terminals. This work proposes a study using Queuing Theory and Computational Modeling, in order to highlight the effective tools and theories that relate and optimize existing processes.